2018
DOI: 10.1016/j.jns.2018.01.026
|View full text |Cite
|
Sign up to set email alerts
|

‘The shock of diagnosis’: Qualitative accounts from people with Motor Neurone Disease reflecting the need for more person-centred care

Abstract: The diagnosis of Motor Neurone Disease (MND) is devastating for people with MND (PwMND) and their families. The objective of this study is to describe the experiences of PwMND in receiving the diagnosis in order to inform a more person-centred approach to communicating such bad news. The design was an anonymous postal survey facilitated by all MND associations across Australia (2014-15). Survey questions centred on the SPIKES protocol for communicating bad news; each question contained an area for written resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…However, 36% to 56% of patients rated their doctor's ability as average or below average [28,29]. Similarly, qualitative studies also revealed mixed results with patients sharing both positive and negative experiences [30,31] although a study of a single centre which was following international guidelines for MND care received only positive feedback [32].…”
Section: Satisfaction With Diagnosis Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…However, 36% to 56% of patients rated their doctor's ability as average or below average [28,29]. Similarly, qualitative studies also revealed mixed results with patients sharing both positive and negative experiences [30,31] although a study of a single centre which was following international guidelines for MND care received only positive feedback [32].…”
Section: Satisfaction With Diagnosis Deliverymentioning
confidence: 99%
“…On the contrary, doctors who were judged to possess poor skills only spent an average of 13.4 minutes on the consultation [29]. Patients were often frustrated with a very short consultation as they did not have the opportunity for discussion [31]. At the same time, they knew the clinicians were in high demand and it could take months for the next appointment [34].…”
Section: Consultation Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report by the Institute of Medicine, Committee on Quality Health Care in America,26 most HCPs stated that their way of working was PCC; however, the patients reported frustration regarding their chance to participate in their own care. Several studies show that HCPs need to shift focus to be more oriented to the patient’s own values, thoughts, and experiences of their illness, to be more person-centered2,3133 rather than based on prevailing norms 34. Previous research points out that HCPs’ own understanding of PCC is of relevance when providing safe care of good quality 35.…”
Section: Introductionmentioning
confidence: 99%
“…Receiving a diagnosis of MND can come as a shock to patients and family members, and people with MND experience a range of emotions when being communicated the diagnosis [7]. Addressing the emotional needs of people with MND influences their quality of life (QoL) [8].…”
Section: Introductionmentioning
confidence: 99%